2023
DOI: 10.1002/med.21941
|View full text |Cite
|
Sign up to set email alerts
|

Research progress in spike mutations of SARS‐CoV‐2 variants and vaccine development

Abstract: The coronavirus disease 2019 (COVID‐19) pandemic can hardly end with the emergence of different variants over time. In the past 2 years, several variants of severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2), such as the Delta and Omicron variants, have emerged with higher transmissibility, immune evasion and drug resistance, leading to higher morbidity and mortality in the population. The prevalent variants of concern (VOCs) share several mutations on the spike that can affect virus characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 240 publications
(624 reference statements)
0
3
0
Order By: Relevance
“…We expected the S gene to contain more non-synonymous mutations. Mutations in the S protein may enhance its interaction with ACE2, help it to escape from the immune system, or improve furin cleavage [2,3,54,55]. It has also been suggested that the S gene is more likely to be single-stranded than other SARS-CoV-2 genes, thus making it a favourable target for C>U deamination and leading to an excessively high mutation rate [56].…”
Section: Most Frequent Snvsmentioning
confidence: 99%

The Mutational Landscape of SARS-CoV-2

Saldivar-Espinoza,
Garcia-Segura,
Novau-Ferré
et al. 2023
IJMS
“…We expected the S gene to contain more non-synonymous mutations. Mutations in the S protein may enhance its interaction with ACE2, help it to escape from the immune system, or improve furin cleavage [2,3,54,55]. It has also been suggested that the S gene is more likely to be single-stranded than other SARS-CoV-2 genes, thus making it a favourable target for C>U deamination and leading to an excessively high mutation rate [56].…”
Section: Most Frequent Snvsmentioning
confidence: 99%

The Mutational Landscape of SARS-CoV-2

Saldivar-Espinoza,
Garcia-Segura,
Novau-Ferré
et al. 2023
IJMS
“…Omicron VOC was identified in November 2021; it quickly replaced the previous Delta variant and became the dominant variant worldwide. The first known genetic lineage of Omicron variant VA.1 features more than 30 mutations in the spike protein [ 56 ]. To date, the omicron variant has completely supplanted all other coronavirus variants.…”
Section: Resultsmentioning
confidence: 99%
“…This scenario partly occurs because the protection provided by different immunization schemes against newer variants depends on previous infections, vaccination, and hybrid immunity ( 1 , 2 ). This situation, added to the selective pressure exerted on the SARS-CoV-2 virus during the pandemic, has led to the sporadic appearance of variants that confer different degrees of resistance ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…pressure exerted on the SARS-CoV-2 virus during the pandemic, has led to the sporadic appearance of variants that confer different degrees of resistance (3,4).…”
mentioning
confidence: 99%